Toward Sensitive Room‐Temperature Broadband Detection from Infrared to Terahertz with Antenna‐Integrated Black Phosphorus Photoconductor. (9th January 2017) - Wang, Lin; Liu, Changlong; Chen, Xiaoshuang; Zhou, Jing; Hu, Weida; Wang, Xiaofang; Li, Jinhua; Tang, Weiwei; Yu, Anqi; Wang, Shao‐Wei; Lu, Wei
Abstract : Graphene‐like two‐dimensional materials (graphene, transition‐metal dichalcogenides (TMDCs)) have received extraordinary attention owing to their rich physics and potential applications in building nanoelectronic and nanophotonic devices. Recent works have concentrated on increasing the responsivity and extending the operation range to longer wavelengths. However, the weak absorption of gapless graphene, and the large bandgap (>1 eV) and low mobility in TMDCs have limited their spectral usage to only a narrow range in the visible spectrum. In this work, we demonstrate for the first time a high‐performance, antenna‐integrated, black phosphorus (BP)‐based photoconductor with ultra‐broadband detection from the infrared to terahertz frequencies. The good trade‐off between the moderate bandgap and good mobility results in a broad spectral absorption that is superior to that of graphene. Different photoconductive mechanisms, such as photothermoelectric (PTE), bolometric, and electron–hole generation can be distinguished depending on the device geometry, incident wavelength, and power. Especially, the photoconductive response remains highly efficient, even when the photon energy is extended to the terahertz (THz) band at room temperature, which is driven by the thermoelectric‐induced well. The proposed photodetectors have a superior performance with an excellent sensitivity of over 300 V W −1, low noise equivalent power (NEP) (smaller than 1 nW Hz −0.5 (10 pW Hz −0.5 ) with respect to the incident (absorbed) power), and fast response, all of which play key roles in multispectral biological imaging, remote sensing, and optical communications. Abstract : A highly efficient room‐temperature black phosphorus (BP) detector is shown that can operate from the infrared to the terahertz bands. The moderate bandgap and high mobility of black phosphorus make it a good candidate for both infrared and terahertz detections. Different detection principles are reported for the antenna‐coupled BP detector, which is based on the photoconductive effect transiting from the interband electron–hole relaxations to intraband wave excitations.